2021
DOI: 10.1002/chem.202101884
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Coplanar Bicyclic Backbones for 1,2,4‐Triazole‐1,2,4‐Oxadiazole‐Derived Energetic Materials

Abstract: Combining different nitrogen‐rich heterocycles into a molecule can fine‐tune its energetic performance and physical properties as well as its safety for use in energetic materials. Here, 1,2,4‐oxadiazole was incorporated into 1,2,4‐triazole to construct new energetic backbones. 3‐(5‐Amino‐1H‐1,2,4‐triazol‐3‐yl)‐1,2,4‐oxadiazol‐5‐amine (5) was designed and synthesized. Nitramino‐functionalized N‐(5‐(5‐amino‐1,2,4‐oxadiazol‐3‐yl)‐3H‐1,2,4‐triazol‐3‐yl)nitramide (6) and N‐(5‐(5‐(nitramino)‐1,2,4‐oxadiazol‐3‐yl)‐3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…It is concluded that the main decomposition products are H 2 O (ν = 3544, 3510 cm −1 ) and CO (ν = 2183, 2150 cm −1 ). 27 This can be reasonably explained as follows: (1) AgCl becomes a molten liquid state at 445 °C. (2) Since the test material we used is an aluminum crucible, AgCl and Al undergo a substitution reaction to obtain Ag and AlCl 3 , and AlCl 3 is a gaseous compound at this temperature, so the quality is lost.…”
Section: Resultsmentioning
confidence: 99%
“…It is concluded that the main decomposition products are H 2 O (ν = 3544, 3510 cm −1 ) and CO (ν = 2183, 2150 cm −1 ). 27 This can be reasonably explained as follows: (1) AgCl becomes a molten liquid state at 445 °C. (2) Since the test material we used is an aluminum crucible, AgCl and Al undergo a substitution reaction to obtain Ag and AlCl 3 , and AlCl 3 is a gaseous compound at this temperature, so the quality is lost.…”
Section: Resultsmentioning
confidence: 99%
“…[35] Nor could the protect-Scheme 1. Synthesis of 1-amino-5-azidotetrazole (1) through diazotization of triaminoguanidinium chloride and nitration using mixed acid to 1-nitrimino-5-azidotetrazole (2).…”
Section: Resultsmentioning
confidence: 99%
“…Alongside ever greater efforts to develop more powerful explosives, the environmental aspect in particular is a central factor for the development of new energetic materials. [1][2][3] For this, some basic properties should be fulfilled, whereby newly developed substances should be free of heavy metals and perchlorates. Compounds containing these components are demonstrably harmful to the environment and hazardous to humans' health.…”
Section: Introductionmentioning
confidence: 99%
“…Samples D1 to D9 were conventional single-compound explosives with higher detonation performance than the tetrazole EMs labeled as D10 to D17. A set of novel constructed coplanar bicyclic backbones for 1,2,4-triazole-1,2,4-oxadiazole-derived high nitrogen energetic compounds 19 were marked as D18 to D27. Besides, their typical detonation parameters, including DV, HoD, VoD, DP, and DT, were calculated by EXPLO5, as shown in Table S1 †.…”
Section: Methodsmentioning
confidence: 99%